Hormonal computing: a conceptual approach - Vallverdú, Jordi; Talanov, Max; Leukhin, Alexey; Fatykhova, Elsa; Erokhin, Victor (Frontiers in Chemistry, 2023)
This paper provides a conceptual roadmap for the use of hormonal bio-inspired models in a broad range of AI, neuro-engineering, or computational systems. The functional signaling nature of hormones provides an example of a reliable multidimensional information management system, able to solve parallel multitasks. Two existing examples of hormonal computing bioinspired possibilities are shortly reviewed, as well as 2 novel approaches are introduced, with a special emphasis on what researchers propose as Hormonal Computing for neurorehabilitation in patients with complete spinal cord injuries. They extend the use of epidural electrical stimulation (EES) by applying sequential stimulations to limbs through prostheses. The prostheses include various limb models and are connected to a neurostimulation bus called the central pattern generator (CPG). The CPG bus utilizes hormonal computing principles to coordinate the stimulation of the spinal cord and muscles.